Computational study of the decomposition mechanisms of ammonium dinitramide in the gas phase. (3rd July 2018) - Wang, Zhiyin; Zhang, Tian-Lei; Li, Ming-Jing; Xu, Qiong; Wang, Rui; Roy, Soumendra; Yu, Xiaohu; Jin, Lingxia
ABSTRACT: CBS-QB3 method has been employed to determine the geometries, the vibrational frequencies of the reactants, the products and the transition states involved in intramolecular hydrogen-transfer and decomposition reactions of the free gas-phase H3 N···HN(NO2 )2 (ADN * ). The results show that the intramolecular hydrogen-transfer reaction of ADN * is more feasible than that of HDN. ADN * and its hydrogen-transfer isomers ADN * -IIa, b, c decompose along four channels to form NH3 + HONO + 2NO (PI ), ȮH + ṄO3 + N2 + NH3 (PII ), ȮH + ṄO2 + N2 O + NH3 (PIII ), and HNO3 + N2 O + NH3 (PIV ), respectively. It has been found that the dominant decomposition channels are PI and PIII . The hydrogen-transfer reaction can reduce the barrier of elimination of NO2 and forming N2 O reactions in ADN * and HDN. The decomposition of ADN * -IIc to form NO2 and N2 O is more feasible than that of the gas-phase HDN. The rate constants ( k ) of rate-determining step of ADN * show that k PI and k PIII are higher than k PIV and k PII . Compared with HDN-IIc → N2 O+ȮH+ṄO2, k PIII of ADN * -IIc is significantly higher than that of k HDN-IIc . These results reveal that NH3 (as a chaperon) has a certain influence on the decomposition mechanisms and kinetics of ADN * . Abstract :